FLUCTUATIONS OF DEVONIAN SEA LEVEL IN THE MOSCOW BASIN - Rodionova G.D.; Umnova V.T. (My University, 1997)
A representative data base is used to elucidate the history of Devonian sedimentation in the Moscow basin of the Russian platform. The Devonian section includes six rhythms of sedimentation and seven principal geological boundaries, whose levels are identified on the basis of miospore, brachiopod, and conodont zonation. The inferred curve of secular variations in the basin salinity is plotted versus palynological and standard conodont zones and correlated with the main stages of sedimentation and sporgenous plant evolution. There is also a positive correlation between the salinity variation in the Devonian Moscow basin and global eustatic events detected by Johnson and Sandberg.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская